Translation Procedure of Religious Term Between Google Translate and DeepL in Indonesia Travel Website - Nur Afifah; Muhammad Farkhan; Moh. Supardi; Hilmi Akmal (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2025)
ABSTRACT: This study aims to analyze how machine translation tools, such as Google Translate and DeepL, translate religious terms on the Indonesia Travel website, a tourism platform rich in cultural and religious elements. This research employed a qualitative method, examining 10 Indonesian English articles and identifying 15 representative religious terms based on AlGhamdi's (2016) classification. The term is translated using both Google Translate and DeepL, and the results are analyzed using Newmark's (1988) translation procedure framework. The findings showed that both machines apply six procedures in handling religious terms, with transference and recognized translation being the most frequently used. However, there are differences in how Google Translate and DeepL strike a balance between accuracy and readability. Google Translate simplifies translations, improving accessibility but risking the loss of cultural nuance. In contrast, Google Translate preserves more of the religious and cultural depth, although this can reduce clarity for general readers. In conclusion, while both machines are effective in handling recognized religious terms, Google Translate is considered more effective for the Indonesia Travel website, as it delivers more transparent and more accessible translations for global audiences. However, post-editing is still recommended to ensure that translations are both accurate and readable.